Behavioral Dilemmas and Support Requirements of Self-Management for Chinese Adolescents with Epilepsy During Transition Readiness: A Mixed-Methods Study - Cui C; Zhou H; Chen W; Li S; Zheng X (Patient Preference and Adherence, 2023)
Cui Cui,1 Hengyu Zhou,2 Wenjin Chen,3 Shuangzi Li,3 Xianlan Zheng1 1Department of Nursing Children’s Hospital of Chongqing Medical University, National Clinical Research Center for Child Health and Disorders, Ministry of Education Key Laboratory of Child Development and Disorders, Chongqing, People’s Republic of China; 2School of Nursing, Chongqing Medical University, Chongqing, People’s Republic of China; 3Neurology Department of Children’s Hospital of Chongqing Medical University, National Clinical Research Center for Child Health and Disorders, Ministry of Education Key Laboratory of Child Development and Disorders, Chongqing, People’s Republic of ChinaCorrespondence: Xianlan Zheng, Tel +8617783864677, Email zhengxianlan@vip.163.comObjective: The study aimed to describe and explore the behavioral dilemmas and support-requirement characteristics of self-management for epileptic adolescents during transition readiness.Methods: A convergent mixed-methods study was conducted. Patients (N=654) in eight hospitals in China completed a demographic and disease characteristics questionnaire and measures of epilepsy transition readiness, self-management of epilepsy, and perceived social support, and 17 patients and family care-givers were interviewed simultaneously.Results: Adolescents with epilepsy (AWEs) had low levels of self-management and transition readiness, and moderate levels of social support. Multivariate linear regression showed that age, antiepileptic drug type, comorbidities, family structure, transition readiness, and social support were statistically significant in the regression model (p< 0.05). Seven themes emerged in the qualitative analysis related to self-management behavioral dilemmas, and 11 themes emerged for support requirements. The findings from the qualitative and quantitative analyses were combined to create a conceptual model based on the SMART framework and the social cognitive theory.Conclusion: The findings indicate that the state of self-management behaviors of Chinese AWEs is not promising. The influential factors and characteristics are complex and systematic.Practice Implications: This study provides insights into the self-management practices of AWEs in China and expands previous self-management and transitional readiness strategies and models.Keywords: convergent mixed-methods, adolescence, self-management of chronic diseases, epilepsy